The Effect of Engine Specifications, Technician Quality, and Bmhp Prices On Hospital Preferences In Nipro Hemodialysis KSO Contracts In Eastern Indonesia - Arif Joko Supriyanto (Jurnal Indonesia Sosial Teknologi, 2024)
The number of people with kidney failure in Indonesia currently reaches 1.6 million people with a prevalence of 6 per mile. The high number of people with kidney failure is caused by 2 main triggers, namely diabetes and hypertension. One form of treatment / treatment for patients with kidney failure is hemodialysis / dialysis using dialyzer services. Hemodialysis treatment can now be done in various health facilities services and is covered by BPJS financing. Hospitals as service providers collaborate with vendors / partners to procure machines and BMHP (Medical Consumables). The high demand for hemodialysis machines makes this industry/business create fierce competition. The form of competition between service provider vendors is in terms of machine specifications, after-sales service, and prices offered by each vendor. The form of cooperation between hospitals and vendors consists of various patterns / schemes. However, a common pattern used in cooperation between hospitals and vendors is in the form of Operational Cooperation (KSO) Consumable Purchases. This study raised the topic of opportunities for extending existing KSO contracts between hospitals and KSO partners, based on the influence of machine specifications, technician quality, and BMHP prices. This study will examine whether or not there is an influence of the three variables mentioned above on the hospital's decision to extend or terminate the KSO contract. The study data used the population of hemodialysis installations in the working area of Eastern Indonesia.